Design and Development of an Educational Vocabulary Game - Permana, Rico Surya; Sukarsa, I Made; Buana, Putu Wira; Wisswani, Ni Wayan (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 6 No 2 (2025): JITTER, Vol.6, No.2, August 2025, 2025)
Language is an essential part of human culture, serving as a tool for communication and identity. In the era of globalization, mastering multiple languages offers cognitive, cultural, academic, and career advantages. However, conventional learning methods often lack engagement for students. This study presents the design and development of Bermain Kata, an interactive educational game aimed at improving vocabulary and language comprehension through various game modes, including word-meaning matching, synonyms, antonyms, and word categories. The application was developed and evaluated based on the ISO 25010 software quality standard, which includes eight key characteristics. Testing results showed an overall score of 3.667, exceeding the eligibility threshold of 2.374 (56% of the maximum score), with seven characteristics rated as Excellent and one as Adequate. These findings indicate that Bermain Kata is a feasible and effective tool to support language learning in Indonesia.